E-logistics managing digital supply chains for competitive advantage - Wang, Yingli (Of Cardiff Business School); Pettit, S. J. (Stephen J.) (Kogan Page, 2021)
E-Logistics serves as the nerve system for the whole supply chain and enables smooth information flow within and between organizations. This new and updated edition provides the latest and most comprehensive coverage on digitalization in logistics and supply chain. It covers all transport modes and the role of ICT in supporting an integrated freight and supply chain network. E-Logistics provides a cross-academic and industry perspective with leading academics and practitioners as contributing authors. A variety of successful e-logistics business approaches are discussed covering a range of commercial sectors and transport modes. Subsequent chapters address in depth support systems for B2C and B2B e-commerce and e-fulfilment, warehouse management, RFID, electronic marketplaces, global supply network visibility and service chain automation. Industry case studies are used to support the discussion. The new edition also covers emerging technologies such as AI, machine learning and autonomous vehicles, Internet of Things, Robotics, drone and last mile deliveries.